Blockchain at the Service of Ocean Challenges: Discard Management and Bycatch Control - Hossein Noroozi; Afshin Abolhasani (International Journal of Marine Engineering Innovation and Research, 2021)
The purpose of this paper is to introduce a new alternative method of seafood management by using blockchain technology with a particular emphasis on bycatch and overfishing. The paper has been investigated through an innovative connection between the various consumers in the world, what we call bycatch can be considered as food for humans, animals, or plants. In addition, numerous parties that are directly or indirectly connected to the seafood industry can utilize the blockchain platform in order to facilitate seafood trading, especially what is called bycatch. The data analyzing in this paper has been clarified using a decentralized management system, seafood resources, and human consumption can stay in a semi-equilibrium. Furthermore, the paper can take the first steps to reduce environmental catastrophes caused by humans on the ocean.